Development of environments to test driver assist functions for reversing an A-double combination vehicle - Parshetti, Vikram; Keshava Reddy, Lohith Reddy; Prabhu, Anand; Ashok, Nrupathunga; Jain, Pratham; Srinivas, Akhil (My University, 2021)
transportation efficiency. These vehicles have multiple trailers pulled by a single tractor and the A-double is an example of such a vehicle. Although A-doubles improve transportation efficiency, they are extremely difficult to manoeuvre in the reverse direction. The work done in the project aims to develop a rapid prototype environment that reduces development time and cost of controllers used to assist drivers in reversing the A-double. The assist functions developed using these environments help improve loading and unloading time while also reducing the stress levels of the driver(s). The testing and validation of the controller is done in two tiers. The first tier is a virtual environment to test the basic functionality and the second tier is a scaled environment to test the robustness and performance of the controller. Two control strategies have been developed to validate the test environments and their performance has been discussed. The performance of the test environments and possible improvements have been discussed.